Application of air ionizer to remove electrostatic discharge (ESD) dust for plastics material in automotive painting process - Yosri, Muhammad Hafizan; Muhamad, Pauziah; Mohd Yatim, Norfazrina Hayati (Penerbit Akademia Baru, 2019)
In the painting production process, repairing of painted defects by running the part through repeat process, together with the essential requirement of quality control routines, contribute for a very large proportion for the operating costs. The dust and fibre defects which ranged between 40% and 50% found to be the highest rejection in of the local painting line manufacturer. Both defect not only affected the visual appearance but also the of the parts performance. The objective of this research is to explore the effectiveness of the air ionizer device to reduce the electrostatic value of the painted material that attract the foreign particle to fall into painted surface. By doing so, the rejection contributes by dust and fibre particle in the automotive painting can be reduce. The ionizer is an effective application to replace the conventional methods which applied the air blow process to remove dust and fibre particle before painting process. The experiment has been conducted by measuring the electrostatic value of the raw material before and after the ionizer treatment. The correlation between the static value and the production pass rate also has been examined. The result shows 0.34% reduction of the fibre particle after the implementation of the ionizer device.